PENGARUH PROFITABILITAS DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN STUDI EMPIRIS PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aulia Rizki Arjanggie; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2015)
This study explain how profitability and age of a company can affect the disclosure of corporate social responsibility in the  annual report. The companies that earn high profit tend to assume that they didn’t need to make a report about things that can interfere their financial succes, so they make an un-optimal performance in social responsibility of their annual report. On the other side, the companies that has a long standing are more experienced in publish their financial statements. With this experiences, they could be more aware of the information needs for their company . For a sample, there are 113 annual reports of basic and chemical industry companies listed in Indonesia Stock  Exchange  during  2010-2012.  The  informations  processing  are  using  multiple  linear regression with profitability and age of a company as the independent variable and the disclosure of corporate social responsibility as the dependent variable. So this study use 3 control variables: firm size, leverage, and capital intensity. The result of this study show that the age of a company doesn’t have any effect on   the disclosure of corporate social responsibility, while profitability could affect the disclosure of corporate social responsibility negatively and justify the concept of legitimacy theory.